The effects of burnout on truck drivers: A study of truck drivers in CityDeep Johannesburg - Kolobe, Mpolokeng Codelia (My University, 2022)
Burnout is conceptualized as the psychological response to chronic work stress, and it is characterized by feeling exhausted. Truck drivers spend most of their time on the road alone, thus making them vulnerable to burnout because of the various job stressors they encounter, such as lack of assistant drivers, rude drivers on the road, lack of sleep, theft and hijacking etc. This study is aimed at exploring the effect that burnout has on truck drivers at a truck depo in Johannesburg. The study, which was conducted at a truck driver depo, adopted a qualitative exploratory approach using case study design. Non-probability sampling, using a purposive sampling technique, was employed to select a sample of eleven truck drivers and two supervisors aged 25 to 50 years. Where consent was given, audio-recorded semi-structured interviews were conducted and later transcribed; alternatively, notes were taken during the interviews. Using multidimensional theory, data was analysed using six steps thematic analysis. The main findings demonstrated that while truck drivers may not know the concept of burnout, they do experience physical and mental sign and symptoms of burnout. The impact of burnout impact their personal and work life is impacted negatively. The findings of this study contribute to the existing knowledge base in the specialised field of occupational social work. The results will be used to inform interventions for preventing and managing burnout in truck drivers effectively in the workplace.
A report on a research study presented in partial fulfilment of the requirements for the degree Master of Arts in the field of Occupational Social Work to the Faculty of Humanities, University of the Witwatersrand, 2021